Azolla An alternative source of feed for poultry farming in north east india - Kumar, Rakesh; Patra, M K; Deka, Bidyut C; Upadhyay, Pravin Kumar (Indian Farming, 2018)
Azolla meal is an unconventional feed ingredient at low price and may be used as poultry feed to reduce the feed cost and has no deleterious effect on palatability of the broilers. Azolla can be used as an ideal feed substitute for cattle, fish, pig and poultry apart from its utility as a biofertilizer for wetland paddy. Azolla meal is a feed ingredient in broiler rations. It is popular and cultivated widely in other countries like China, Vietnam and Philippines etc. and is yet to be taken up in India in a big way. The production technology has to be standardized to the diverse and different agroclimatic zones of the country, to enable its wider spread.